Regeneration of Subcutaneous Cartilage in a Swine Model Using Autologous Auricular Chondrocytes and Electrospun Nanofiber Membranes Under Conditions of Varying Gelatin/PCL Ratios - Zheng, Rui; Wang, Xiaoyun; Xue, Jixin; Yao, Lin; Wu, Gaoyang; Yi, Bingcheng; Hou, Mengjie; Xu, Hui; Zhang, Ruhong; Chen, Jie; Shen, Zhengyu; Liu, Yu; et al. (Frontiers in Bioengineering and Biotechnology, 2021)
The scarcity of ideal biocompatible scaffolds makes the regeneration of cartilage in the subcutaneous environment of large animals difficult. We have previously reported the successful regeneration of good-quality cartilage in a nude mouse model using the electrospun gelatin/polycaprolactone (GT/PCL) nanofiber membranes. The GT/PCL ratios were varied to generate different sets of membranes to conduct the experiments. However, it is unknown whether these GT/PCL membranes can support the process of cartilage regeneration in an immunocompetent large animal model. We seeded swine auricular chondrocytes onto different GT/PCL nanofiber membranes (GT:PCL = 30:70, 50:50, and 70:30) under the sandwich cell-seeding mode. Prior to subcutaneously implanting the samples into an autologous host, they were cultured in vitro over a period of 2 weeks. The results revealed that the nanofiber membranes with different GT/PCL ratios could support the process of subcutaneous cartilage regeneration in an autologous swine model. The maximum extent of homogeneity in the cartilage tissues was achieved when the G5P5 (GT: PC = 50: 50) group was used for the regeneration of cartilage. The formed homogeneous cartilage tissues were characterized by the maximum cartilage formation ratio. The extents of the ingrowth of the fibrous tissues realized and the extents of infiltration of inflammatory cells achieved were found to be the minimum in this case. Quantitative analyses were conducted to determine the wet weight, cartilage-specific extracellular matrix content, and Young’s modulus. The results indicated that the optimal extent of cartilage formation was observed in the G5P5 group. These results indicated that the GT/PCL nanofiber membranes could serve as a potential scaffold for supporting subcutaneous cartilage regeneration under clinical settings. An optimum GT/PCL ratio can promote cartilage formation.